Degradation experiment on water samples collected from Kevo, Utsjoki region in Finland during June 2023 - Tuomela, Nea; Elovaara, Samu; Kaartokallio, Hermanni; Hultman, Jenni; Thomas, David N (In: Tuomela, N et al. (2025): Dissolved organic matter properties and processing in a small arctic catchment with peatland and palsa features [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.981156, 2025)
This table contains measurements collected during a biodegradation experiment that was initiated immediately after collecting the samples and terminated approximately 6 months later. Some samples were filtered through a 0.8 µm membrane filter, as shown by the filter pore size parameter, to remove grazers. The experiment was conducted in the dark at 10 °C. Samples were stored in 500 mL glass bottles that were stirred regularly, except dissolved oxygen samples for respiration measurements, which were stored in separate glass stopper vials. The date time recordings within each event show the initial measurement and subsequent measurements of that sample. Other data represent direct measurements at the given time, but respiration shows the daily oxygen consumption between the initial measurement at the start of the experiment and the next measurement after approximately two weeks.
Keywords: Arctic; Bacteria; biogeochemistry; CDOM; Laboratory experiment; Palsa; Peatland; river